Pengaruh Remote Working Terhadap Employee Engagement dan Produktivitas Pekerja Generasi Z Di Bandung Raya - Setiawan, Viatri Annisa Putri; Kiki Sudiana (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study explores the impact of remote working on employee engagement and productivity among Generation Z workers in Greater Bandung. As post-pandemic work patterns shift toward digital and flexible arrangements, understanding how remote work affects younger employees becomes increasingly important. The research employed a quantitative method with descriptive and verification approaches, collecting data from 400 Generation Z workers through structured questionnaires. Analysis was conducted using descriptive statistics and multiple linear regression. Findings indicate that remote working positively affects employee engagement and productivity, provided it is supported by effective management practices. Nevertheless, issues such as employee loyalty and alignment between job tasks and individual competencies remain critical challenges. This study contributes practical recommendations for organizations in designing remote work policies tailored to the characteristics of younger employees. It also provides theoretical contributions to human resource management literature in the digital era. Future research is encouraged to include respondents from multiple generations and additional variables such as work-life balance, communication patterns, or leadership styles to gain a broader understanding of remote work dynamics.